Wagner Handbuch - Lütteken, Laurenz; Groote, Inga Mai; Meyer, Michael; Wagner, Richard (Bärenreiter ; Metzler, 2012)
Breit angelegtes Handbuch, das sich mit Richard Wagners Leben und Werk systematisch befasst. (LK/S: Voss-Krueger)